PENGARUH LINGKUNGAN KERJA DAN REKAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN BAGIAN SERVICE PADA PT. RIAU JAYA CEMERLANG PEKANBARU - Dina Christina; Marzolina '; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted on a PT. Riau Jaya Cemerlang Pekanbaru in order to determine what variables influence of enviromental variables and co-workers working simultaneously and partially on employee job satisfaction service PT. Riau Jaya Cemerlang, in Pekanbaru.As for the population in this study is part of a service employee PT. Riau Jaya Cemerlang, in Pekanbaru which amounted to 55 people and populations sampled in this study by using the method of census of all employees. Analysis of the data used is descriptive analysis, as it also uses the quantitative analysis using multiple linear regression with SPSS version 18:00 From the results of testing that has been done, simultaneous regression test (F-test) showed that the work environment and co-workers simultaneously significant effect on employee satisfaction service PT.Riau Jaya Cemerlang, in Pekanbaru. Partial Test Results (t test) indicate that the work enviroment variable positive and significant effect on employee job satisfaction service, and coworkers variable partial positive and significant effect on job satisfaction of employees in service. Recommendations that can authors ask is that companies should pay attention to the working environment and a good co-worker relationship to improve employee job satisfaction in the future.Keywords:Work enviromental, Coworkers, and Job Satisfaction